Perbedaan Peningkatan Kemampuan Representasi Matematis dan Self Confidence Siswa pada Pembelajaran Berbasis Masalah dan Pembelajaran Biasa - Cut Yuniza Eviyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine the differences in increasing students' mathematical representation ability and self-confidence in problem based learning (PBM) and ordinary learning (PB). In addition to seeing whether there is an interaction between learning and students' initial mathematical ability (KAM) to increase students' mathematical representation ability and whether students' self-confidence increases. The study population was all students of SMP Negeri 1 Lhokseumawe. The sample of the study was taken randomly by 2 classes totaling 60 students. Data analysis was performed with Two Path ANAVA. The results of the study, students' mathematical representation ability can be known based on the F value on the learning factors (PBM and PB) of 76.4 with a significance value of 0.00 less than α 0.05. While the F value is based on KAM 65.8 with a significance level of 0.00. Conclusion, Improvement of mathematical representation ability and self confidence of students who are given PBM models are higher than students who are given PB, and there is no interaction between learning models and KAM on increasing students' mathematical representation ability, and there is no interaction between learning models and KAM towards increasing self student confidence. Keywords: Problem Based Learning Model, Ordinary Learning, Mathematical Representation, Self Confidence.